2015
DOI: 10.1007/s10147-015-0854-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in robotic surgery for rectal cancer

Abstract: Robotic technology, which has recently been introduced to the field of surgery, is expected to be useful, particularly in treating rectal cancer where precise manipulation is necessary in the confined pelvic cavity. Robotic surgery overcomes the technical drawbacks inherent to laparoscopic surgery for rectal cancer through the use of multi-articulated flexible tools, three-dimensional stable camera platforms, tremor filtering and motion scaling functions, and greater ergonomic and intuitive device manipulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Robotic systems offer the advantages of: (i) a stable camera platform that is directly controlled by the surgeon; (ii) 3D stereoscopic vision with 10× magnification; and (iii) instruments with 7 degrees of movement, assisted by tremor‐filtering and motion‐scaling . These features potentially translate to better surgical outcomes in terms of preservation of neurological function, earlier return of bowel function, greater rates of negative resection margin, reduced fatigue of the surgeon, and lower conversion rates …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic systems offer the advantages of: (i) a stable camera platform that is directly controlled by the surgeon; (ii) 3D stereoscopic vision with 10× magnification; and (iii) instruments with 7 degrees of movement, assisted by tremor‐filtering and motion‐scaling . These features potentially translate to better surgical outcomes in terms of preservation of neurological function, earlier return of bowel function, greater rates of negative resection margin, reduced fatigue of the surgeon, and lower conversion rates …”
Section: Discussionmentioning
confidence: 99%
“…in 2002 . Since then, various authors have attempted to expound on the advantages of robotic surgery . Unfortunately, these benefits have to date been limited by issues such as prolonged docking time, operative duration, technical difficulties in multi‐quadrant access, and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery has a number of benefits including flexible devices with seven degrees of free movement, stable three‐dimensional camera platforms and more precise surgical manipulation from tremor filtering and motion scaling . Baek et al .…”
Section: Discussionmentioning
confidence: 99%
“…stable three-dimensional camera platforms and more precise surgical manipulation from tremor filtering and motion scaling [59,60]. Baek et al have shown that RoTME may have advantages in a narrow pelvis or lowlying rectal cancer [61].…”
Section: Discussionmentioning
confidence: 99%
“…As the pelvic autonomic nerves are outside the mesorectum, this technique also allows better preservation of the urinary and sexual functions. [10][11][12][13] Initially, during the 1980s, TME was performed by open surgery, which is still acceptable and commonly used in the treatment of rectal cancer. Currently, minimally invasive surgery techniques, such as laparoscopy and robotic surgery, are gaining popularity.…”
Section: Introductionmentioning
confidence: 99%